El sistema aeróbico y su efectividad en el tiro al gol en jóvenes futbolistas - Constante Acosta, Alex Fabricio (2024)
Soccer is one of the most followed and popular sports in the world, even becoming a social phenomenon. In this sport, aerobic exercises are used in sports training for many purposes and their effectiveness has been demonstrated in several studies, however, they have not been delved into in-depth correspondence with playing positions. The thesis presented is titled "The aerobic system and its effectiveness in shooting goals in young soccer players." It was developed with the objective of Assessing the effectiveness of the aerobic exercise system in shooting on goal in young people from the Llamingos FC Permanent Soccer School. in the province of Chimborazo. It responds to a mixed quasi-experimental research approach, developed with a sample of 12 male athletes between the ages of 14 and 18. Aerobic exercises were applied for 12 weeks in three mesocycles. The results were evaluated and could be verified through the goal shooting test, with the help of the Beep Test Leger Running phone application, which facilitated the calculation of the main parameters. in which the substantial increase in aerobic capacity and effectiveness in shooting on goal in general was confirmed.